Implementation of wireless data collection system - Zhong, Kaixun (2008)
This project is to study the concept of a wireless data collection system, then design and implement a system for the application of monitoring real-time WeiQi game. The system is able to monitor the targeted environment, process signal, transmit data through wireless channel and present received data in an appropriate manner. In addition, the system is capable of handling different applications concurrently.